Effects of geometrical dimensions of flow channels of a large-active-area PEM fuel cell: A CFD study. (9th April 2021) - Carcadea, Elena; Ismail, Mohammed S.; Ingham, Derek Bin; Patularu, Laurentiu; Schitea, Dorin; Marinoiu, Adriana; Ion-Ebrasu, Daniela; Mocanu, Dan; Varlam, Mihai
Abstract: Various flow field designs have been numerically investigated to evaluate the effect of pattern and the cross-sectional dimensions of the channel on the performance of a large active area PEM fuel cell. Three types of multiple-serpentine channels (7-channels, 11-channels and 14-channels) have been chosen for the 200 cm 2 fuel cell investigated and numerically analysed by varying the width and the land of the channel. The CFD simulations showed that as the channel width decreases, as in the 14-channels serpentine case, the performance improves, especially at high current densities where the concentration losses are dominant. The optimum configuration, i.e. the 14-channels serpentine, has been manufactured and tested experimentally and a very good agreement between the experimental and modelling data was achieved. 4 channel depths have been considered (0.25, 0.4, 0.6 and 0.8 mm) in the CFD study to determine the effects on the pressure drop and water content. Up to 7% increase in the maximum reported current density has been achieved for the smallest depth and this due to the better removal of excess liquid water and better humidification of the membrane. Also, the influence of the air flow rate has been evaluated; the current density at 0.6 V increased by around 25% when air flow rate was increased 4 times; this is attributed to better removal of excess liquid water. Graphical abstract: Image 1 Highlights: A 200 cm 2 PEM fuel cell has been numerically and experimentally investigated. Effects of multiple-serpentine channels are investigated in real size PEM fuel cells. Fuel cell performance significantly improves with decreasing channel width and depth. Higher flow rate of air influence the reactants uniformity and water removal. A better insight into the real size PEMFC influence on scaling up the manufacturing process.